2004
DOI: 10.1038/sj.ijo.0802852
|View full text |Cite
|
Sign up to set email alerts
|

Concept of fat balance in human obesity revisited with particular reference to de novo lipogenesis

Abstract: The measurement of fat balance (fat input minus fat output) involves the accurate estimation of both metabolizable fat intake and total fat oxidation. This is possible mostly under laboratory conditions and not yet in free-living conditions. In the latter situation, net fat retention/mobilization can be estimated based on precise and accurate sequential body composition measurements. In case of positive balance, lipids stored in adipose tissue can originate from dietary (exogenous) lipids or from nonlipid prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 38 publications
1
32
1
1
Order By: Relevance
“…This is in agreement with previous studies where lower expression of FASN was seen in adipose tissue of obese individuals, despite this group having increased hepatic lipogenesis compared with the lean [13], and where lower expression of FASN was seen in adipose tissue of obese individuals irrespectively of diet [35]. Other studies have not found any clear evidence that DNL is more active in adipose tissue obtained from obese individuals [36], even following a high carbohydrate diet [12]. In contrast to our findings, Berndt et al [14] recently found increased FASN expression in the adipose tissue of obese compared with lean individuals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies where lower expression of FASN was seen in adipose tissue of obese individuals, despite this group having increased hepatic lipogenesis compared with the lean [13], and where lower expression of FASN was seen in adipose tissue of obese individuals irrespectively of diet [35]. Other studies have not found any clear evidence that DNL is more active in adipose tissue obtained from obese individuals [36], even following a high carbohydrate diet [12]. In contrast to our findings, Berndt et al [14] recently found increased FASN expression in the adipose tissue of obese compared with lean individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Together with our results, this implies that lipogenic genes do not seem to be expressed in tandem in the liver and adipose tissue, and may even be regulated in a reciprocal fashion. Dietary composition is known to have a large influence on hepatic and adipose DNL [36]. In our study, the participants were following their habitual diet, and no correlation was seen between adipose tissue DNL gene expression and carbohydrate or fat, or indeed total energy intake (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…[1][2][3][4] Here, we extended these concepts to relate quantitatively the longitudinal body composition changes with adaptations of substrate utilization. Although Forbes's logarithmic body composition relationship was used for illustrative purposes in the present study, the same analysis could be applied to any function relating longitudinal changes of lean mass to fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, it remains to be elucidated exactly how longitudinal body composition changes are quantitatively related to the properties of macronutrient balance. Here, we asked the following question: how must substrate utilization quantitatively adapt to a given energy imbalance to produce the longitudinal body composition changes proposed by Forbes 5 ?…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that this was indicative of a decrease in fat oxidation and decreased rate of de novo lipogenesis [31]. These both seem unlikely since levels of lipid oxidation among the quinoa and the control diet did not differ [31] and furthermore, increased, rather than decreased de novo lipogensis from carbohydrate would lead to an increase in the RQ value [34].…”
Section: Effects On Weight Gainmentioning
confidence: 99%